PENDIDIKAN SEKS DALAM AL-QUR’AN; PERSPEKTIF TAFSIR TARBAWI TENTANG LARANGAN MENDEKATI ZINA - Fatih, Muhammad (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2018)
Al-Qur'an contains many terms that contain sexual content both directly (mubasyarah) and symbolic (kinayah), including furuj (genitals), semen (sperm), nuthfah (mixing of male and female sperm), arham (womb), al-mass (contact, conjugal relationship), al-lams (contact, conjugal relationship), preacher (contact, conjugal relationship), rafats (words and actions that lead to bodily relationships) , bigha '(prostitution), adultery, fahisyah (vile deeds), abkar (virgin), murawadah (seducing), and so forth. In general the mention of the above terms in the Qur'an covers four contexts; first, the context of the explanation of halal and haram law. Second, the context of scientific knowledge in verses about the creation of humans. Third, the historical context in the stories in the Qur'an, and fourth, the context of the language in which the Qur'an outlines issues of sexuality in polite, symbolic language. Talks about sexuality and sex education are by no means the invitation to pornography, or the spread of atrocities among humans, or encourage people to commit adultery or do damage. One of the themes of sex education in the Qur'an is the prohibition of adultery. This theme is becoming increasingly interesting for several reasons. First, the prohibition of adultery is narrated by the Qur'an with the expression